Quality Classification of Groundwaters of Western Rajasthan - Gupta, S C (Annals of Arid Zone, 2016)
An integrated classification of quality of groundwater based upon EC, SAR and RSC values of 4145 water samples has been made to evaluate water quality for irrigation in 11 districts of western Rajasthan. It is observed that groundwaters are sodic in character due to high SAR or RSC values. The SAR ranges from 0.15 to 176.8 with an average value of 13.9. In districts Barmer. Bikaner and Jaisalmer more than 33.3 per cent waters have SAR more than 18. High RSC generally occurs in low to medium salinity v.aters and ranges from nil to 68.8 meL-1 with an average value of 3.1 meL-1.The districts viz., Jhunjhunu, Nagaur and Stkar have high RSC in ground waters. Based upon salinity, SAR and RSC distribution, the whole region has been divided in six saline-sodic zones.